Efektivitas Polyvinyl Acetate (PVAc) Sebagai Matriks Pada Komposit Sampah - Masturi, Masturi; Mikrajuddin, Mikrajuddin; Khairurrijal, Khairurrijal (BERKALA FISIKA, 2010)
It was fabricated a composite using solid waste as filler and polyvinyl acetate (PVAc) as matrice. This work is as a solution of more serious solid waste problems. The solid waste used is paper waste and leaf one with their composition are 60% and 40% respectively. The crushed-solid waste then hot-pressed at 100 MPa of pressure and 150Â°C of temperature. Then, the compressive strength of composite before and after PVAc presence was investigated to get a composition in which the compressive strength is optimum. Â  Keywords: composite, solid waste, polyvinyl acetate, compressive strength.